PERNIKAHAN SIRI DALAM PERSPEKTIF PASAL 402 KITAB UNDANG-UNDANG HUKUM PIDANA - Natasya Dwi Aprilia; Haifa Yasyfi Ramadhani; Vanisha Lorin Isma; Mahatma Naufal Fabian Prasetyo; Bhanu Rasendriya; Deliana Sevyanada Senjaya; Darto Darto (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
A nikah siri is a marriage that fulfills all the requirements and essential elements of a valid marriage under Islam but is not officially registered before a state-recognized marriage registrar. This practice raises serious legal conflicts, particularly with Law No. 1 of 2023 on the New Criminal Code, which includes Article 402. This article could criminalize unregistered marriages. This study conducts an in-depth analysis of: (1) Can a religiously valid nikah siri be subject to criminal punishment by the state? (2) Do the elements of “legal impediment” and “concealment of status” in Article 402 automatically apply to all nikah siri, or only to cases of fraud? (3) What is the legal position of Islam through ushul fiqh and maqasid al-sharia? (4) Is this criminalization consistent with the principles of hifz al-din and hifz al-nasl? (5) What are the legal implications for women and children? The research methodology is appropriate, employing a legal, conceptual, and case study approach. The results show that Article 402 of the Criminal Code does not directly criminalize all unregistered marriages, but only those involving fraud, such as intentionally concealing one’s marital status or legal impediments. From an Islamic legal perspective, the obligation to register marriages can be justified as ta’zir and sadd al-dzari’ah, but criminalizing a valid sharia marriage contract contradicts hifz al-din. In conclusion, this policy is half-hearted and conflicts with Islam. The recommendation is to amend the regulations to be more equitable and to strengthen the marriage validation (isbat) process as a more reasonable solution.